2019
DOI: 10.1182/blood-2019-123169
|View full text |Cite
|
Sign up to set email alerts
|

Updated Meta-Analysis of Randomized Controlled Trials to Evaluate the Incidence of Infection and Pneumonia in Patients with Multiple Myeloma Treated with Daratumumab

Abstract: Introduction: Multiple myeloma is a hematologic cancer of plasma cell, a blood cell which normally produce antibodies, and accounts for approximately 13% of all hematologic malignancies. Daratumumab is a human anti CD38 IgGκ monoclonal antibody with a well characterized mechanism of action via direct antitumor effects and an immunomodulatory component and the incorporation of daratumumab to standard multiple myeloma regimen has shown to significantly improve response rates and survival, with not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The strength of this study is that we have investigated both TD and TI B-cell responses in the presence of DARA with a strong impact on TD stimulation and—in this respect—a differential outcome of different B-cell subsets, demonstrating the most impact of CD38 targeting on the activation and maturation of memory B cells into PBs and PCs. Although derived from an in vitro system, our findings do suggest a possible mechanism for the additional risk of bacterial and viral infections in MM patients receiving anti-CD38–directed therapies in vivo ( 50 , 51 ). Where normally the barrier of immunological memory would protect patients, reduced recall responses by memory B cells upon TI or TD stimulation leave patients who receive DARA treatment prone to infections with common pathogens ( 16 ).…”
Section: Discussionmentioning
confidence: 78%
“…The strength of this study is that we have investigated both TD and TI B-cell responses in the presence of DARA with a strong impact on TD stimulation and—in this respect—a differential outcome of different B-cell subsets, demonstrating the most impact of CD38 targeting on the activation and maturation of memory B cells into PBs and PCs. Although derived from an in vitro system, our findings do suggest a possible mechanism for the additional risk of bacterial and viral infections in MM patients receiving anti-CD38–directed therapies in vivo ( 50 , 51 ). Where normally the barrier of immunological memory would protect patients, reduced recall responses by memory B cells upon TI or TD stimulation leave patients who receive DARA treatment prone to infections with common pathogens ( 16 ).…”
Section: Discussionmentioning
confidence: 78%
“…A meta-analysis of 3547 patients enrolled in 5 phase III trials showed a higher incidence of all grades of infection when daratumumab was added to other agents (relative risk [RR] = 1.27, 95% confidence interval [CI] = 1.13-1.44, P = 0.0001), with high-grade pneumonia in newly diagnosed patients carrying the highest risk. 50 Potential challenges in interpreting these data include overlapping pulmonary symptoms (eg, cough, dyspnea) secondary to CD38-induced basophil degranulation and leukotriene production following initial infusions; however, early recognition, infectious agent diagnosis, and supportive intervention are critical. Grade 3/4 neutropenia following single-agent daratumumab is 20% and increases to >80% in combination regimens.…”
Section: Infectious Considerationsmentioning
confidence: 99%